Analysis of the Value of Ability to Pay & Willingness to Pay Toll Tariffs in the People of Gresik Regency Based on the Facilities and Infrastructure of the Krian – Legundi – Bunder Toll Road - Brian V P, Andreas; Teki Tjendani, Hanie; Wulandari, Esti (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to determine the toll rates desired by the people of Gresik Regency based on the value of Ability to Pay (ATP) and Willingness to Pay (WTP) on the Krian – Legundi – Bunder (KLB) Toll Road. Through traffic count surveys and Road Side Interviews (RSI) at toll gates and arterial roads, data on vehicle population, payment ability, and user preferences for existing toll rates were obtained. The analysis employed a Logit model to evaluate the relationship between the ATP and WTP values and their correlation with the current toll rates. The results revealed that both the WTP and ATP of the community were lower than the existing toll tariff. Specifically, the study found that the optimal toll rate for users would be Rp. 1,100/km, which is 26.96% lower than the current rate of Rp. 1,506/km. This adjustment not only aligns better with the financial capacities of the users but also presents an opportunity for revenue optimization. By lowering the toll rate, it is predicted that increased traffic volume could compensate for the reduced fee, ultimately benefiting both the toll operator and the community. In conclusion, establishing a toll rate that reflects user preferences is crucial for enhancing accessibility and ensuring sustainable revenue generation for infrastructure development.